CAMPURAN KAPUR DALAM PEMBUATAN BATAKO ABU - Sapulette, Denisa; Nanlohy, Ansye; Tuanakotta, Abraham (Journal Agregate, 2024)
Brickstone is a material for building house walls made from cement, aggregate, and water. Brick stones are widely used in house construction as a substitute for bricks to speed up construction. Recently, many additional materials have been used as alternatives to reduce high construction costs. One way is using household materials, namely ash from burning, because they are easy to obtain. Therefore, the idea of ​​making bricks using a mixture of lime and burning ash is expected to produce bricks with better characteristics, with fine compressive strength by SNI. In this research, bricks were made with dimensions of 25 cm long, 13 cm wide, and 10 cm high. With a composition of 200 grams of lime, 1500 grams of ash, 1000 grams of sand, and 2000 grams of water. With a total of 3 test objects, the age of the test objects to be tested is 28 days. The average compressive strength test results of ash bricks for the 3 test objects were 8.7 kg/cm2. Following SNI 03-0349-1989 concerning physical requirements for bricks, the average compressive strength value for class IV is 25 kg/cm2. Based on these requirements, ash bricks mixed with lime do not meet SNI.